PENGARUH MODEL PEMBELAJARAN READING QUESTIONING AND ANSWERING (RQA) MELALUI VIRTUAL CLASS TERHADAP KETERAMPILAN METAKOGNITIF DAN HASIL BELAJAR KOGNITIF MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI PADA MATA KULIAH KEMAMPUAN DASAR MENGAJAR - La Ode Muhammad Azhar; Chumidach Roini; Said Hasan (EDUKASI, 2021)
This study aims to determine the effect of the Reading Questioning And Answering (RQA) learning model through Virtual Class on metacognitive skills and cognitive learning outcomes of students in the biology education study program in the basic teaching ability course. There are two variables in this study, namely the independent variable is the Reading Questioning And Answering (RQA) Learning Model and the dependent variable is Metacognitive Skills and Cognitive Learning Outcomes. The method used in this research is a quantitative method. The form of research used is a quasi-experimental research design with pretest posttest control group design. Data collection techniques using the Metacognitive Awareness Inventory (MCAI) Questionnaire, Cognitive Learning Outcomes Test and Documentation. The results of this study indicate that there is an effect of the Reading Questioning And Answering (RQA) learning model through the Virtual Class on metacognitive skills and cognitive learning outcomes of students of the biology education study program in the subject of basic teaching abilities.